Model to Simulate Brain Biopsies Using a Navigated Robotic Guiding System and a Bone Cutting Laser - Tu Ha Thanh; Luder Yann; Röthlisberger Michel; Schicker Martina; Morawska Marta; Cordier Dominik (Current Directions in Biomedical Engineering)
Brain biopsies are necessary in cases of unclear lesions on imaging studies to establish a treatment plan based on the histologic diagnosis. A previous study investigated the potential of lasers to make brain biopsies less invasive, faster and safer. The study demonstrated that lasers can create highly precise burr holes which themselves can act as a sufficient guide for the biopsy needle. Furthermore, lasers can create tangential canals in the bone which allows to biopsy brain regions that are usually impossible or hazardous to access. Building upon the results of the previous study, further research and technological advancements were pursued. This includes a biopsy needle attachment for the robot, which will be used to simulate brain biopsies using CARLO© (Cold Ablation Robot-guided Laser Osteotome) with its Er:YAG laser and navigated robotic guiding system. The study utilizes five freshly frozen skulls, which are immobilized using a Mayfield clamp. Prior to conducting the experiment, the NeuroPlan© software is employed to plan the path and angle of the biopsies. To align the preexperimental CT with the skull, referencing points on the skull and its surface are registered using a pointer. A small skin incision is performed to reach the area of bone where the laser ablates the bone for the biopsy. Preliminary experimental results suggest that the combined use of laser ablation and a guidance device enables precise bone ablation and accurate needle guidance for biopsies. These initial results demonstrate the potential of integrating laser technology and robotics in neurosurgery, potentially enabling less invasive, faster and safer biopsies, ultimately leading to better patient outcomes.